Higher Justice in the Screen Images of Sherlock Holmes and Father Brown / Воплощение идеи высшей справедливости в экранных образах Шерлока Холмса и отца Брауна - BULGAROVA BELLA A. / БУЛГАРОВА Б.А.; OVCHARENKO ALEXEY YU. / ОВЧАРЕНКО А.Ю.; BARABASH VICTOR V. / БАРАБАШ В.В.; VOROPAEVA YULIA A. / ВОРОПАЕВА Ю.А. (Наука телевидения, 2023)
The article covers various aspects of how the idea of higher justice is embodied in the screen images of classic amateur detectives Father Brown and Sherlock Holmes. The first part of the article presents a semantic systematization of scientific and popular science works on screen incarnations of the image of Sherlock Holmes. There are no similar works on Father Brown, which, among other aspects, determines the scientific novelty of our article. The article also provides a comparative analysis of the idea of justice and its later on-screen representations in the Russian and European socio-cultural traditions. The second part focuses on the results of the empirical research that gives an insight into psychological perception of Father Brown and Sherlock Holmes screen images in the film adaptation of The Adventures of Sherlock Holmes, a British detective series (1984–1993); and in Father Brown— a detective series on BBC One (2013–present). As a result of the conducted research it was concluded that the image of Sherlock Holmes is a more popular and timeless embodiment of the idea of higher justice due to the lack of semiotic bindings to personal identity factors, including confessional ones. On the other hand, the idea of higher justice, embodied in the image of Father Brown, correlates not so much with reason as with the inner moral law of I. Kant, represented in human conscience. However, the Catholic pathos of this idea (extremely important for G.K. Chesterton) in the image of Father Brown does not make the image purely confessional, limited only by the framework of one religious doctrine. The practical significance of the research presented in the article lies in the fact that its results can be used not only in the curriculum of students of directing and filmmaking departments in terms of how exactly the genre of the classic English detective story should be interpreted in modern film adaptations, but also for developers of multimedia environment in their unique creative work with various types of texts of modern culture (physical, verbal, visual, digital). В статье анализируются различные аспекты кинематографического воплощения идеи высшей справедливости в экранных образах классических сыщиков-любителей — отца Брауна и Шерлока Холмса. В первой части статьи представлена смысловая систематизация научных и научно-популярных работ об экранных воплощениях образа Шерлока Холмса. Аналогичных работ об отце Брауне нет, что, в том числе, определяет научную новизну нашей статьи. Также дан сравнительный анализ идеи справедливости и ее позднейшего экранного воплощения в российской и европейской социо-культурной традиции. Во второй части приведены и проанализированы результаты эмпирических исследований психологии восприятия экранных образов отца Брауна и Шерлока Холмса в экранизации «Приключения Шерлока Холмса» — британский детективный сериал производства (1984–1993); и «Отец Браун» — детективный сериал телеканала BBC One (2013 – по настоящее время). В итоге проведенного исследования сделаны выводы о том, образ Шерлока Холмса является более популярным и вневременным воплощением идеи Высшей справедливости из-за отсутствия семиотических связей с личной идентичностью, в том числе конфессиональной. С другой стороны, идея Высшей справедливости, воплощенная в образе отца Брауна, соотносится не столько с разумом, сколько с внутренним нравственным законом И. Канта, выраженным в человеческой совести. Католический пафос этой идеи, чрезвычайно важной для Г. К. Честертона, в образе отца Брауна не делает его при этом узко конфессиональным, ограниченным рамками одной религиозной доктрины. Практическая значимость представленных в статье исследований заключается в том, что их результаты могут быть использованы не только в учебной программе студентов режиссерских и киноведческих факультетов с точки зрения того, как именно следует трактовать жанр классического английского детектива в современных экранизациях, но и для создателей мультимедийной среды в их творческой конкретной работе с различными видами текстов современной культуры (вещественных, вербальных, визуальных, цифровых).